Evening high‐intensity interval exercise does not disrupt sleep or alter energy intake despite changes in acylated ghrelin in middle‐aged men. Issue 6 (29th March 2019) - Larsen, Penelope; Marino, Frank; Melehan, Kerri; Guelfi, Kym J; Duffield, Rob; Skein, Melissa
Abstract : New Findings: What is the central question of this study? What are the interactions between sleep and appetite following early evening high‐intensity interval exercise (HIIE)? What is the main finding and its importance? HIIE can be performed in the early evening without subsequent sleep disruptions and may favourably alter appetite‐related hormone concentrations. Nonetheless, perceived appetite and energy intake do not change with acute HIIE regardless of time of day. Abstract: Despite exercise benefits for sleep and appetite, due to increased time restraints, many adults remain inactive. Methods to improve exercise compliance include preferential time‐of‐day or engaging in short‐duration, high‐intensity interval exercise (HIIE). Hence, this study aimed to compare effects of HIIE time‐of‐day on sleep and appetite. Eleven inactive men undertook sleep monitoring to determine baseline (BASE) sleep stages and exclude sleep disorders. On separate days, participants completed 30 min HIIE (60 s work at 100% V ̇ O 2 peak, 240 s rest at 50% V ̇ O 2 peak ) in (1) the morning (MORN; 06.00–07.00 h), (2) the afternoon (AFT; 14.00–16.00 h) and (3) the early evening (EVEN: 19.00–20.00 h). Measures included appetite‐related hormones (acylated ghrelin, leptin, peptide tyrosine tyrosine) and glucose pre‐exercise, 30 min post‐exercise and the next morning; overnight polysomnography (PSG; sleep stages); and actigraphy, self‐reported sleep and food diaries for 48 h post‐exercise. There were no between‐trial differences for total sleep time ( P  = 0.46). Greater stage N3 sleep was recorded for MORN (23 ± 7%) compared to BASE (18 ± 7%; P  = 0.02); however, no between‐trial differences existed ( P  > 0.05). Rapid eye movement (REM) sleep was lower and non‐REM sleep was higher for EVEN compared to BASE ( P  ≤ 0.05). At 30 min post‐exercise, ghrelin was higher for AFT compared to MORN and EVEN ( P  = 0.01), while glucose was higher for MORN compared to AFT and EVEN ( P  ≤ 0.02). No between‐trial differences were observed for perceived appetite ( P  ≥ 0.21) or energy intake ( P  = 0.57). Early evening HIIE can be performed without subsequent sleep disruptions and reduces acylated ghrelin. However, perceived appetite and energy intake appear to be unaffected by HIIE time of day. Abstract :